Beliefs and perceptions about HACCP in childcare centers: an exploratory study - Riggins, Lynn D. (Kansas State University, 2006)
This research developed a model to assess beliefs and perceptions of employees about following a Hazard Analysis and Critical Control Points (HACCP) -based food safety program in Childcare Centers. The four Health Belief Model constructs included perceived susceptibility, severity, benefits, and barriers. Because of their proven worth in behavioral research, the constructs behavioral intention and self-efficacy were added to the model. An instrument designed to test the model was mailed to directors and foodservice employees at accredited Childcare Centers in six Midwestern states (n = 528). The final response rate was 17.5 percent. Self-efficacy was tested as a moderator between the independent variables and behavioral intentions. Exploratory factor analysis identified factors. Most items loaded as expected, but the construct perceived severity loaded on two factors requiring an additional factor in the model. The final factor names included perceived susceptibility, center consequences, child consequences, perceived benefits, perceived barriers, self-efficacy, and behavioral intentions. The model accounted for 70.07% of the variance for a six-factor model. Perceived benefits and self-efficacy significantly affected behavioral intentions to follow a HACCP-based food safety program. In addition, self-efficacy had a moderating effect on the relationship between perceived benefits and behavioral intentions. Results indicated that directors and foodservice employees understood that children are susceptible to foodborne illnesses. However, they did not believe that a foodborne illness could occur at their Center, and if it did, there would be no consequences to themselves or the Center. Improved construct items need to be developed and tested utilizing a population that has more knowledge about HACCP-based food safety programs. This model should be tested with other populations that are familiar with HACCP-based food safety programs to determine if perceived susceptibility, severity, or barriers have an impact on behavioral intentions to follow a HACCP-based food safety program. Once beliefs and perceptions about food safety practices and behaviors are identified, interventions can be tailored to address specific misconceptions resulting in improved food safety practices and behaviors.
Keywords: childcare; HACCP; Home Economics (0386)